Impact of Illness Severity and Interventions on Successful Weaning from Nasal CPAP in Very Preterm Neonates: An Observational Study - I-Ling Chen; Hsiu-Lin Chen (MDPI AG, 2022)
This study aims to identify clinical variables that could affect successful weaning from nasal continuous positive airway pressure (NCPAP) in very preterm infants. Infants born at a gestational age (GA) of <32 weeks were retrospectively enrolled. Weaning from NCPAP was initiated when the infants were clinically stable. In the univariate analysis, GA, birth weight, body weight (BW) z-score at the time of successful NCPAP weaning, intubation, total duration of intubation, respiratory distress syndrome grade, APGAR score at the 1 and 5 min, initial shock, anemia, bronchopulmonary dysplasia, number of blood transfusions, total duration of dopamine use, administration of more than two doses of surfactant, use of aminophylline, use of a diuretic, and total duration of total parenteral nutrition were significantly associated with postmenstrual age (PMA) at the time of successful NCPAP weaning. Multivariate analysis showed that the total duration of intubation, bronchopulmonary dysplasia, and administration of more than two doses of surfactant were positively associated with PMA at the time of successful NCPAP weaning. A reverse association was noted between BW z-score and PMA at the time of successful NCPAP weaning. Sufficient nutrition and avoidance of further ventilator-induced lung injury could decrease NCPAP duration in very preterm infants.